let $ f\in F[x] $ be a polynomial. and prove that the matrix $ f\left(J_{n}\left(\lambda\right)\right) $ satisfies

$ [f\left(J_{n}\left(\lambda\right)\right)]_{ij}=\begin{cases} \frac{1}{\left(j-i\right)!}f^{(j-i)}\left(\lambda\right) & 1\leq i\leq j\leq n\\ 0 & else \end{cases} $

when $ f^{(j-i)} $ is the (j-i) deriviative of $ f $.

Here's what i tried:

step 1: I proved that

$ [\left(J_{n}\left(0\right)\right)^{k}]=\begin{cases} 1 & j=i+k\\ 0 & else \end{cases} $

step 2: Using the binom formula, I proved that

$ \left(J_{n}\left(\lambda\right)\right)^{k}=\sum_{i=0}^{k}\binom{k}{i}\lambda^{k-i}\left(J_{n}\left(0\right)^{i}\right) $

Now assume $ f\left(x\right)=\sum_{j=0}^{k}a_{j}x^{j} $ then,

$ f\left(J_{n}\left(\lambda\right)\right)=\sum_{j=0}^{k}a_{j}\left(J_{n}\left(\lambda\right)^{j}\right)=\sum_{j=0}^{k}a_{j}\sum_{i=0}^{j}\binom{j}{i}\lambda^{j-i}\left(J_{n}\left(0\right)\right)^{i}=\sum_{j=0}^{k}\sum_{i=0}^{j}a_{j}\lambda^{j-i}\left(J_{n}\left(0\right)\right)^{i} $

Im not sure how to recognize the (j-i) deriviative out of the expression. And I'm not sure how to continue. Any ideas will help. Thanks in advance.

  • $\begingroup$ Couldn't find the proof yet. A solution can be really helpful. $\endgroup$
    – FreeZe
    May 31 '20 at 14:14


Your step 1 is OK.

Your step 2 also, but you're not using it completely. During the step 2, you're considering I imagine $f_k(x) = x^k$. Therefore

$$f_k^{(l)}(x)= \begin{cases} \frac{k!}{(k-l)!} x^{k-l} & \text{ for } 0 \le l \le k\\ 0 & \text{ else} \end{cases}$$

Use this and your step 1 to prove the expected formulae for the monomial $f_k(x) = x^k$.

Your last step could be a single sentence noticing that the requested formulae is linear in $f$ as the derivation is.

  • $\begingroup$ Im sorry I dont understand how it is connected to the rows and columns of the matrix. the i,j term of the matrix should be equal to the (j-i) deriviative multiply by $ 1/{(j-i)!} $ and I cant see how to proceed with your hint. also I cant see why your hint is correct. I would say $ f_{k}^{(l)}\left(x\right)=\begin{cases} \frac{k!}{l!}x^{k-l} & 0\leq l\leq k\\ 0 & else \end{cases} $ rather than what you suggested $\endgroup$
    – FreeZe
    May 30 '20 at 15:15
  • $\begingroup$ I think that my formulae for the derivation of $f_k$ is correct. Take $l=0$ for example and then proceed by induction. Regarding the hint, use the formulae that you got at step 1 in your step 2 with the derivation formulae that I gave. $\endgroup$ May 30 '20 at 15:21
  • $\begingroup$ Do you think that for a general polynomial $ f_{k}\left(x\right)=\sum_{j=0}^{k}a_{j}x^{j} $ this formulae will work ? : $ f_{k}^{(l)}\left(x\right)=\begin{cases} \sum_{j=0}^{k}a_{j}\frac{j!}{(j-l)!}x^{k-l} & 0\leq j\leq l\leq k\\ 0 & else \end{cases}$ Also, the lower bound of the polynomial is 0 while the lower bound in the matrix would be 1 (the first row/column) how do you suggest fixing it? $\endgroup$
    – FreeZe
    May 30 '20 at 15:32
  • $\begingroup$ $ f\left(J_{n}\left(\lambda\right)\right)=\sum_{j=0}^{k}a_{j}\left(J_{n}\left(\lambda\right)\right)^{j}=\sum_{j=0}^{k}\sum_{i=0}^{j}\binom{j}{i}a_{j}\lambda^{j-i}J_{n}^{i}\left(0\right)=\sum_{i=0}^{j}\frac{1}{i!}f^{(i)}\left(\lambda\right)J_{n}^{i}\left(0\right) $ It does look closer to the form i want to get to. But still, I dont know how to proceed. can you elaborate ? $\endgroup$
    – FreeZe
    May 30 '20 at 15:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.